Nitrogen-Doped Nanoporous Carbon/Graphene Nano-Sandwiches: Synthesis and Application for Efficient Oxygen Reduction - Wei, J.; Hu, Y.; Liang, Y.; Kong, B.; Zhang, J.; Song, J.; Bao, Q.; Simon, G.; Jiang, San Ping; Wang, H. (Wiley-VCH Verlag, 2015)
A zeolitic-imidazolate-framework (ZIF) nanocrystal layer-protected carbonization route is developed to prepare N-doped nanoporous carbon/graphene nano-sandwiches. The ZIF/graphene oxide/ZIF sandwich-like structure with ultrasmall ZIF nanocrystals (i.e., ≈20 nm) fully covering the graphene oxide (GO) is prepared via a homogenous nucleation followed by a uniform deposition and confined growth process. The uniform coating of ZIF nanocrystals on the GO layer can effectively inhibit the agglomeration of GO during high-temperature treatment (800 °C). After carbonization and acid etching, N-doped nanoporous carbon/graphene nanosheets are formed, with a high specific surface area (1170 m2 g−1). These N-doped nanoporous carbon/graphene nanosheets are used as the nonprecious metal electrocatalysts for oxygen reduction and exhibit a high onset potential (0.92 V vs reversible hydrogen electrode; RHE) and a large limiting current density (5.2 mA cm−2 at 0.60 V). To further increase the oxygen reduction performance, nanoporous Co-Nx/carbon nanosheets are also prepared by using cobalt nitrate and zinc nitrate as cometal sources, which reveal higher onset potential (0.96 V) than both commercial Pt/C (0.94 V) and N-doped nanoporous carbon/graphene nanosheets. Such nanoporous Co-Nx/carbon nanosheets also exhibit good performance such as high activity, stability, and methanol tolerance in acidic media.